Cognitive skill instruction on enhancing retention in pupils with mild intellectual disability - Longpoe, Patricia Kwalzoom; Adebisi, Rufus Olanrewaju (Journal of Social, Humanity, and Education, 2023)
Purpose: This study aimed to determine the effectiveness of cognitive skill instruction on pupils with mild intellectual disability retention in spelling exercises, retaining poems, and letter recognition. Research methodology: Research questions and hypotheses were formulated as a part of the methodology. This study used a non-equivalent pre-test, post-test, experimental, and control group design. Working memory is the cognitive skill chosen by the researchers. Flash cards, 100 frequency words, and the working rating scale were used to measure working memory in order to examine the cognitive skills of retention of pupils with mild intellectual disability. The study included ten (10) pupils. While the other five pupils comprised the control group, they did not receive any intervention strategy. Five of the ten pupils were in the experimental group and received an intervention package. The instrument was reliable with a reliability index of 0.85 and was valid for its intended use in measuring the required area. Six weeks were spent on the treatment. The t-test for independent samples was used to examine the treatment results. Results: The study's findings showed that parents had an impact on their children's cognitive development and abilities, and special educators had a significant impact on a child's ability to remain in school. Limitations: The researchers suggest that cognitive skill instruction should be implemented in educational settings. Contribution: This research will provide special educators, parents, and the government with information on how well cognitive skills can help students with mild intellectual disability retain information.